Implementasi Pembelajaran Berbasis Media Puzzle Selai Dalam Meningkatkan Hasil Belajar di Sekolah Dasar - Mar’atus Sholichah; Sugiarti Sugiarti; Prilia Rahmadina (UMSU, 2023)
Based on the results of the numerical diagnostic assessment analysis of students in class IV-A, the average score is still low, students still have difficulty answering questions about equivalent fraction material. This is due to a lack of concentration in class, students are passive in learning, and teachers do not use interesting learning media to convey mathematics learning material, especially equivalent fraction material. This study aims to improve mathematics learning outcomes in equivalent fraction material in class IV A SDN Mojorejo 01 Batu City which consists of 27 students. This study used the classroom action research method which was carried out in 2 cycles with each cycle lasting 2 learning meetings. The data collection techniques used were observation, tests, documentation, and interviews, then a quantitative descriptive analysis was carried out based on the data obtained. The research results obtained: 1) The class average at the pre-cycle stage was 56.04 with a classical completeness percentage of 22.22%; 2) The class average in first cycle increased to 69.03 with a classical completeness percentage of 48.14%; and 3) The class average in the secong cycle increased to 88.14 with a classical completeness percentage of 96.29%. Based on the results of the study, it can be concluded that the use of the media puzzle concept of equivalent fractions (puzzle selai) can improve mathematics learning outcomes in the material of equivalent fractions in class IV A SDN Mojorejo 01 Batu City because it has achieved classical mastery ≥ 75% and class average value ≥ 75.